2010
DOI: 10.1096/fj.10-165902
|View full text |Cite
|
Sign up to set email alerts
|

Genetically determined angiotensin converting enzyme level and myocardial tolerance to ischemia

Abstract: Angiotensin I-converting enzyme (ACE; kininase II) levels in humans are genetically determined. ACE levels have been linked to risk of myocardial infarction, but the association has been inconsistent, and the causality underlying it remains undocumented. We tested the hypothesis that genetic variation in ACE levels influences myocardial tolerance to ischemia. We studied ischemia-reperfusion injury in mice bearing 1 (ACE1c), 2 (ACE2c, wild type), or 3 (ACE3c) functional copies of the ACE gene and displaying an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 43 publications
(26 reference statements)
1
26
0
Order By: Relevance
“…In contrast to the reduction in infarct size produced by short-term ACE inhibitor and ARB administration, [23][24][25][26][27][28][29] we and others 39 showed that short-term aliskiren administration did not produce cardioprotection, despite reduction in angiotensin peptide levels. Rather, a longer period of aliskiren administration, sufficient to increase tissue kallikrein protein and mRNA and bradykinin levels, 12 was required to produce cardioprotection.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the reduction in infarct size produced by short-term ACE inhibitor and ARB administration, [23][24][25][26][27][28][29] we and others 39 showed that short-term aliskiren administration did not produce cardioprotection, despite reduction in angiotensin peptide levels. Rather, a longer period of aliskiren administration, sufficient to increase tissue kallikrein protein and mRNA and bradykinin levels, 12 was required to produce cardioprotection.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure was done as previously described (Griol-Charhbili et al, 2005;Messadi-Laribi et al, 2007;Messadi et al, 2010). The left anterior descending coronary artery was occluded 2 mm from the tip of the left atrium for 30 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Angiotensin-Converting Enzyme Inhibitors/ Angiotensin II Receptor Type 1 Receptor Antagonists ACE inhibitors and angiotensin II receptor type 1 (AT1) receptor antagonists when administered before ischemia and/or reperfusion reduce irreversible myocardial injury (Jalowy et al, 1998;Jancso et al, 2004;Messadi et al, 2010). However, the beneficial effects of ACE inhibitors and/or AT1 receptor antagonists become attenuated when cyclooxygenase-2 (COX-2) inhibitors are simultaneously applied (Jalowy et al, 1998).…”
Section: B-adrenoceptor Antagonistsmentioning
confidence: 99%